The Relationship Between Knowledge and Attitudes About Fast Food and Nutritional Status Among Adolescents at SMA IT Nur Hidayah Sukoharjo - Firda Dwi Anggriany; Sudrajah Warajati Kisnawaty; Nur Lathifah Mardiyati (JURNAL KESMAS DAN GIZI (JKG), 2026)
Adolescence is a period of rapid growth that increases nutritional requirements, making adolescents more susceptible to nutritional problems when their dietary patterns are not balanced. One contributing factor is the frequent consumption of fast food, which is typically high in energy, fat, and sugar. This study aims to examine the relationship between knowledge and attitudes regarding fast food and the nutritional status of adolescents at SMA IT Nur Hidayah Sukoharjo. This observational research employed a cross-sectional design and involved 77 students selected through cluster random sampling. Data on knowledge and attitudes were collected using structured questionnaires, while nutritional status was assessed through anthropometric measurements. The data were analyzed using the Chi-Square test. The results indicate that most respondents were within the normal nutritional status category, although several were classified as overweight. While the majority of students demonstrated adequate to good knowledge of fast food, their attitudes toward fast food consumption were generally less favorable. Statistical analysis showed no significant association between knowledge and nutritional status (p=0.353), nor between attitudes and nutritional status (p=0.350). The study concludes that adequate knowledge does not necessarily correspond to optimal nutritional status, as attitudes toward fast food consumption are influenced by multiple factors. Therefore, efforts to improve adolescents' nutritional status should not only focus on providing nutritional information but also on fostering healthier attitudes and eating behaviors.